Seed Germination Studies in Saraca asoca (Roxb.) De Wilde - Gurudev Singh, B.; Warrier, Rekha R.; Anandalakshmi, R.; Sivakumar, V.; Sivalingam, R.; Mahadevan, N. P.; Chevanan, G. (Indian Forester, 2005)
No abstract